Robotic surgical approach in lung cancer: integrative literature review (Research, Society and Development, 2021)
Lung cancer occurs due to the disordered growth of lung cells with smoking being the most prevalent risk factor. Surgical resection is the standard treatment for all solitary pulmonary nodules, except those with benign conditions. Recently, robotic surgery has been shown to be safe and effective, and an excellent alternative to videothoracoscopy. This article aimed to compare the techniques of robotic surgical resection and videothoracoscopy for lung cancer. An integrative review was conducted, which analyzed scientific articles published between the years 2011 to 2021 on the PubMed platform, using the descriptors: lung cancer, surgery, robotic surgery. Eight publications were found and analyzed, with the year 2016 being the most prevalent with 50% of the publications. Analyzing the study locations 3 articles were conducted in China (37.5%). The results of using robotics showed promising and feasible. Regarding VAST, it showed to be a good technique but with vision limitations. On the other hand, RAST brought a three-dimensional vision, besides the precise control. Robotic surgery allows 3D visibility, precision of movements, increasing angulation and safety, reducing hospitalization time and postoperative complications. Furthermore, there are limitations such as lack of an assistant, high costs, lack of studies, and inexperience of surgeons. However, in the future, it is expected that there will be improvement of the technique so that it will be less dependent due to a greater amount of studies and continue with its benefits.